FUNGSI TERDEKATI DAN SIFAT-SIFATNYA - Abdul Aziz; Susilo Hariyanto; Y.D. Sumanto; Solikhin Solikhin (Diponegoro University, 2018)
In this paper, we have defined an approachable function using a simple function on a compact sets. Furthermore the simple properties of the function was examined and it was obtained that measurable function, continuous function, and bounded function are approachable function along the function space is a linier space.